Evidence of Mesozoic multiple hydrothermal activity in the basement at Nonnenmattweiher (southern Schwarzwald), Germany - Wernicke, Rolf Stephan; Lippolt, Hans J. (Mineralium deposita, 1997)
Two botryoidal hematites from the qtz-fl-hem veins at the Nonnenmattweiher cirque (zone of Badenweiler-Lenzkirch, Südschwarzwald) were dated using the (U + Th)-He method. One hematite gives an Early Triassic age (234 ± 5 Ma) and the second straddles the Cretaceous/Jurassic time boundary (126 ± 4 Ma). The ages bracket the ∼entire age spectrum reported to date for Mesozoic vein-type mineralizations in the Schwarzwald. The maximum sedimentary overburden and associated palaeo-temperatures (>130 °C) in the basement of the southern Schwarzwald during the Jurassic did not cause severe age-resetting of the hematites. This implies that both ages probably are formation ages rather than ages of cooling, provided that the 4He retentivities of both hematites are similar. The fact that two hematites from the veins at Nonnenmattweiher yield highly discordant Mesozoic ages suggests multiple hydrothermal activity during the Mesozoic. A previously published age of two adularia (∼155 Ma), intermediate between the hematite ages, supports this view.
Gesehen am 01.12.2022